Identification of renal cyst cells of type I Nephronophthisis by single-nucleus RNA sequencing - Wang, Qianying; Zou, Baojuan; Wei, Xiaoya; Lin, Hongrong; Pang, Changmiao; Wang, Lei; Zhong, Jinglin; Chen, Huamu; Gao, Xuefei; Li, Min; Ong, Albert C. M.; Yue, Zhihui; et al. (Frontiers in Cell and Developmental Biology, 2023)
Abstract Background: Nephronophthisis (NPH) is the most common genetic cause of end-stage renal disease (ESRD) in childhood, and NPHP1 is the major pathogenic gene. Cyst formation at the corticomedullary junction is a pathological feature of NPH, but the mechanism underlying cystogenesis is not well understood. The isolation and identification of cystic cell subpopulations could help to identify their origins and provide vital clues to the mechanisms underlying cystogenesis in NPH. Methods: Single-nucleus RNA sequencing (snRNA-seq) was performed to produce an atlas of NPHP1 renal cells. Kidney samples were collected from WT (Nphp1+/+) mice and NPHP1 (Nphp1del2-20/del2-20) model mice. Results: A comprehensive atlas of the renal cellular landscape in NPHP1 was generated, consisting of 14 basic renal cell types as well as a subpopulation of DCT cells that was overrepresented in NPHP1 kidneys compared to WT kidneys. GO analysis revealed significant downregulation of genes associated with tubular development and kidney morphogenesis in this subpopulation. Furthermore, the reconstruction of differentiation trajectories of individual cells within this subpopulation confirmed that a specific group of cells in NPHP1 mice become arrested at an early stage of differentiation and proliferate to form cysts. we demonstrate that Niban1 is a specific molecular marker of cystic cells in both mice and human NPHP1. Conclusion: In summary, we report a novel subpopulation of DCT cells, marked by Niban1, that are classified as cystic cells in the NPHP1 mice kidney. These results offer fresh insights into the cellular and molecular basis of cystogenesis in NPH. Keywords: Renal cyst; Niban1; Single-nucleus RNA sequencing; Nephronophthisis; NPHP1